Comparative study of conventional Ziehl−Neelsen and bleach concentration method in detecting acid-fast bacilli in fine-needle aspiration material of lymph nodes - Parnajeet Mandal; Soma Ghosh; Abhijit Banerjee; Uma Banerjee (Wolters Kluwer Medknow Publications, 2021)
Background: Tuberculosis (TB), specific infectious disease, affects most of the organs of the human body. Extrapulmonary TB manifests commonly as lymphadenopathy. Emergence of acquired immunodeficiency syndrome warrants the rapid diagnosis to limit its spread. Aim and Objectives: The application of bleach concentration method in detecting tubercle bacilli in the material obtained by fine-needle aspiration (FNA) of lymph nodes, evaluating sensitivity of bleach concentration method over conventional direct smear method in diagnosing tubercular lymphadenitis, detecting bacilli in the background of granuloma formation. Materials and Methods: The prospective, hospital-based, cross-sectional study was carried out in a study population of 78 patients where 15 cases got eliminated following the cytological diagnosis of malignancy and inadequacy of sample. Patients with lymphadenopathy underwent FNA after clinical examination, history taking, and informed consent. The aspirated material was stained with Leishman, H and E, conventional Ziehl−Neelsen (ZN), and bleach concentration method. Data were collected and statistical analysis done. Results: The predominant age group affected was (16-30) years with male preponderance. 44.44% cases were cytomorphologically diagnosed with tuberculous lymphadenitis. Acid-fast Bacilli (AFB) was found in 23 cases by conventional ZN method and 39 cases by bleach concentration method. Sensitivity of bleach method was 92.35% compared to 54.76% in conventional ZN method. Bacilli positivity was more in cases presenting with necrosis than with granuloma alone. Conclusion: Bleach method for detecting AFB is more sensitive than conventional ZN method. It is safe, inexpensive, easy to perform, requires no additional equipment, and safe to handle in laboratory.